Effectiveness of Saccharomyces cerevisiae-fermented rice bran in cadmium immobilization in cadmium-contaminated soil and rice plants - Meirindany, Tina; Nurmaini, Nurmaini; Indirawati, Sri Malem; Ashar, Taufik (Journal of Degraded and Mining Lands Management, 2026)
Agricultural land around the Medan Industrial Estate (KIM) 3 is currently facing a serious threat from cadmium (Cd) contamination, which impacts food security. This study aimed to evaluate the potential of Saccharomyces cerevisiae-fermented rice bran in suppressing the availability and accumulation of Cd in rice plants grown on Cd-contaminated soil. The treatments tested were P0 (control), P1 (100 g S. cerevisiae), P2 (125 g S. cerevisiae), and P3 (150 g S. cerevisiae), with each treatment mixed with 300 g rice bran and applied to 100 m2 of land cultivated with rice plants. The results showed that P3 was the most effective treatment for reducing Cd concentration in rice grain from 0.2 ppm to 0.010 ppm, below the Indonesian Food and Drug Supervisory Agency (BPOM) threshold. The P3 treatment also significantly improved pH and the availability of N, P, and K nutrients of the soil, leading to better plant growth and grain yield. An effective immobilization mechanism that inhibits the translocation of metals into plant tissues makes this innovation a practical, economical, and applicable solution for farmers to restore land function while ensuring food security.